2017
DOI: 10.1111/jam.13436
|View full text |Cite
|
Sign up to set email alerts
|

Selective method for identification and quantification ofBifidobacterium animalissubspecieslactisBB-12 (BB-12) from the gastrointestinal tract of healthy volunteers ingesting a combination probiotic of BB-12 andLactobacillus rhamnosusGG

Abstract: This method will enable more detailed and specific studies of BB-12 in probiotic supplements, including when in combination with LGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…A background of organisms like the ones consumed was detected by the used primer sets. This is not uncommon and has been reported in other fecal detection studies, see, e.g., in [11]. However, after consumption, the levels of these organisms markedly and significantly increased.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…A background of organisms like the ones consumed was detected by the used primer sets. This is not uncommon and has been reported in other fecal detection studies, see, e.g., in [11]. However, after consumption, the levels of these organisms markedly and significantly increased.…”
Section: Discussionsupporting
confidence: 80%
“…The studies that have reported on fecal detection are commonly focusing on a single probiotic strain. Studies that have reported on the fecal recovery of strain combinations have usually focused on strains from different genera, e.g., Bifidobacterium and Lactobacillus [11,12]. Here, we report on the detection of two species from two different genera following their consumption by patients on antibiotic therapy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Suppressing the intestinal infective bacteria, producing some vitamins, anti-cancer and anti-mutation properties, immune system stimulation, reducing blood serum cholesterol, and increasing calcium absorption are some of its other beneficial effects. Bifi dobacterium lactis is the most usable Bifidobacteria in probiotic dairy products (dos Santos Cruxen et al 2017, Gomes and Malcata 1999, Monteagudo-Mera et al 2016, Novak and Katz 2006, Poutsiaka et al 2017.…”
Section: Introductionmentioning
confidence: 99%